RIMA DAN RITME DALAM KUMPULAN PUISI NYANYI SUNYI KARYA AMIR HAMZAH - Satria Sutrisno Sutrisno; Syafrial '; Nursal Hakim Hakim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study is titled Rhyme and Rhythm in Collection of Poems Sing Silent by Amir Hamzah. This study aimed to describe the rhyme assonance, to describe alliteration rhyme, to describe perfect rhyme, to describe imperfect rhyme, to describe duplicate rhyme, to describe croos rhyme, to describe hug rhyme, to describe broken rhyme, to describe continues rhyme, and to describe rhythm of repetition sounds/ word. The method used is descriptive method with qualitative approach. This study is the array of data-lines contained in the poem rhyme assonance, alliteration, perfect, imperfect, double, cross, hug, broken, continue, and rhythm repetition of sound/word. The result of 16 studies found the data of 24 poema. As for the data covers, assonance rhyme 10 data, alliteration 13 data, perfect 6 data, imperfect 12 data, double 4 data, cross 7 data, hug 4 data, broken 12 data, continued 3 data, and rhythm repetition of sound/word 7 data. The dominant rhyme is the alliteration, imperfect, and broken rhyme. Keywords : Rhyme and Rhythm in poetry